Skill differences and wage-effort relationship: Who are more exploited, high-skilled or low-skilled workers? - Hyun Woong Park; Dong-min Rieu (University of Massachusetts, Department of Economics, 2023)
Who are more exploited, high-skilled or low-skilled workers? We address this question using the efficiency wage model with skill differentials incorporated. We perform simulations to find the Nash equilibrium numerically, and our central results are the following. First, higher-skilled workers are offered higher wages but exert less effort, and in particular the skill-wage relationship matches the observed data on wage inequality of the U.S. Second, we employ two measures of the degree of exploitation. On the one hand, the ratio between effort and wage the higher-skilled workers experience is lower than that of lower-skilled workers. This is due to their higher fallback positions which provide them with stronger negotiation power vis-á-vis their employers. On the other hand, in terms of the effort-wage ratio adjusted by skill, it is higher for higher-skilled workers when the range of skill is from zero to around 80th percentile but the ratio falls precipitously as skill increases. The workers with the highest level of skill experience zero degree of exploitation in terms of both measures.
Keywords: B51; 330; Exploitation; efficiency wage model; skill; effort